2012
DOI: 10.1016/j.jmacro.2012.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Does the exchange rate pass-through into prices change when inflation targeting is adopted? The Peruvian case study between 1994 and 2007

Abstract: pe (G. Rodriguez). 1 Throughout this paper the concept of exchange rate pass-through into prices (import, producer, or consumer prices) makes reference to the exchange rate variations' effect over the variations of the respective price index, provided that the former is due to an exchange rate shock. When the price index is not specified, it must be understood that the paper is referring to the exchange rate pass-through into the consumer prices. Journal of Macroeconomicsj o u r n a l h o m e p a g e : w w w .… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 32 publications
0
3
1
1
Order By: Relevance
“…The results are robust to two different events that took place alongside the enactment of the Law: the IT adoption and the broader de-dollarization process. First, while there is prior evidence that the IT regime is associated with a lower ERPT at the aggregate level (Maertens et al, 2012;Winkelried, 2014), we find that the Law played a key role in reducing the ERPT for a specific set of goods at the disaggregate level. These results may point to some degree of complementarity between both policies: the IT regime played a role in reducing the ERPT at the macro level, while the Law on local currency pricing had the largest impact in diminishing the ERPT at the micro level, particularly for A.2 Non-dollarized prices and imported content…”
Section: Discussioncontrasting
confidence: 51%
See 2 more Smart Citations
“…The results are robust to two different events that took place alongside the enactment of the Law: the IT adoption and the broader de-dollarization process. First, while there is prior evidence that the IT regime is associated with a lower ERPT at the aggregate level (Maertens et al, 2012;Winkelried, 2014), we find that the Law played a key role in reducing the ERPT for a specific set of goods at the disaggregate level. These results may point to some degree of complementarity between both policies: the IT regime played a role in reducing the ERPT at the macro level, while the Law on local currency pricing had the largest impact in diminishing the ERPT at the micro level, particularly for A.2 Non-dollarized prices and imported content…”
Section: Discussioncontrasting
confidence: 51%
“…For example, the 2002-2017 year-end 12-month inflation average was 2.8 percent, lower than the 1992-2001 average of 15.3 percent. 25 The previous works that study the impact of the IT adoption on the ERPT in Peru are Maertens et al (2012) and Winkelried (2014). Both use the aggregate CPI and time series methodologies and find that the ERPT falls after implementation of the IT, because of the lower exchange rate uncertainty associated with the IT.…”
Section: Robustness Checks 81 Inflation Targetingmentioning
confidence: 99%
See 1 more Smart Citation
“…The Dornbusch-Overshooting Model explains that differences between short-run and long-run exchange rates and price deviations from the equilibrium point in the short-run cause changes in the inflation rate. The research that found differences in the amount of exchange rate pass-through in countries that adopted inflation-targeting policies was Odria et al (2012); Shintani et al (2013); Dilla (2014); Anh et al (2018); Pham et al (2020); . This study uses data from middle-income countries (South Africa, Brazil, India, Indonesia, and Mexico) and high-income countries (Australia, Canada, Japan, Norway, and Sweden).…”
Section: Figure 4: Transmission Of Exchange Rate Influence On Inflationmentioning
confidence: 99%
“…El presente estudio toma de muestra a Colombia, Chile, México y Perú. Precisamente, a partir del año 2003, dichas economías comienzan a coincidir con un nuevo régimen monetario, el cual ha generado mayor estabilidad y reducción del traspaso (Sansone y Justel, 2015;Mujica, 2015;Maertens et al 2012;Winkelried, 2011).…”
Section: Introductionunclassified